Cardiovascular disease mortality in Asian Americans - Jose, Powell O; Frank, Ariel T H; Kapphahn, Kristopher I; Goldstein, Benjamin A; Eggleston, Karen; Hastings, Katherine G; Cullen, Mark R; Palaniappan, Latha P (Journal of the American College of Cardiology, 2014)
Asian Americans are a rapidly growing racial/ethnic group in the United States. Our current understanding of Asian-American cardiovascular disease mortality patterns is distorted by the aggregation of distinct subgroups. The purpose of the study was to examine heart disease and stroke mortality rates in Asian-American subgroups to determine racial/ethnic differences in cardiovascular disease mortality within the United States. We examined heart disease and stroke mortality rates for the 6 largest Asian-American subgroups (Asian Indian, Chinese, Filipino, Japanese, Korean, and Vietnamese) from 2003 to 2010. U.S. death records were used to identify race/ethnicity and cause of death by International Classification of Diseases-10th revision coding. Using both U.S. Census data and death record data, standardized mortality ratios (SMRs), relative SMRs (rSMRs), and proportional mortality ratios were calculated for each sex and ethnic group relative to non-Hispanic whites (NHWs). In this study, 10,442,034 death records were examined. Whereas NHW men and women had the highest overall mortality rates, Asian Indian men and women and Filipino men had greater proportionate mortality burden from ischemic heart disease. The proportionate mortality burden of hypertensive heart disease and cerebrovascular disease, especially hemorrhagic stroke, was higher in every Asian-American subgroup compared with NHWs. The heterogeneity in cardiovascular disease mortality patterns among diverse Asian-American subgroups calls attention to the need for more research to help direct more specific treatment and prevention efforts, in particular with hypertension and stroke, to reduce health disparities for this growing population.